Adapting to Online Education: A Case Study of Resilience and Innovation in Private Tutoring During the Pandemic - Surya Jatmika; Laili Khasanah; Happy Martama; Puspita Pertiwi (Universitas Muhammadiyah Surakarta, 2024)
During the pandemic, online-based learning faced numerous challenges, such as internet connectivity issues, difficulties in comprehension, an increase in assignments, one-sided interactions, and reduced concentration. Nevertheless, private tutoring institutions emerged as invaluable resources, enabling students to revisit lesson materials, enhance their understanding, and complete assignments effectively. This study aimed to investigate the digital transformation at Prima Utama Private Tutoring Institution in Surakarta, Indonesia, focusing on the factors that support and hinder the institution's operations, and proposing solutions to overcome these obstacles during the pandemic. Utilizing a qualitative case study approach, the research involved institutional leaders, tutors, and students as key informants. Data were collected through interviews, observations, and documentation, followed by data condensation, presentation, and conclusion drawing. The findings demonstrated the institution’s resilience through the implementation of both online and offline tutoring programs, incorporating diverse learning strategies such as lectures, interactive teaching methods, and the use of various applications. Despite technical challenges like network issues and limited technological proficiency, the interaction between tutors and students remained strong. Challenges included physical distance constraints, module availability, and promotional barriers. Proposed solutions included enhancing the Wi-Fi network, providing training on learning platforms, accessing e-modules, and developing practice questions. Additionally, the study recommended using social media, parent testimonials, and discount offers to overcome promotional challenges. Ultimately, this research offers valuable insights into the adaptation of educational institutions during the pandemic and provides recommendations for improving learning quality in an all-digital private tutoring environment.